Development of real-time and lateral flow recombinase polymerase amplification assays for rapid detection of Schistosoma mansoni - Mesquita, Silvia Gonçalves; Lugli, Elena Birgitta; Matera, Giovanni; Fonseca, Cristina Toscano; Caldeira, Roberta Lima; Webster, Bonnie (Frontiers in Microbiology, 2022)
Background: Accurate diagnosis followed by timely treatment is an effective strategy for the prevention of complications together with reducing schistosomiasis transmission. Recombinase Polymerase Amplification (RPA) is a simple, rapid, sensitive, and specific isothermal method with low resource needs. This research aimed at the development and optimisation of a real-time (RT) and a lateral-flow (LF) RPA assay for the detection of S. mansoni. Methodology: RPA reactions were performed at full- (as recommended) and half-volumes (to reduce costs), with fluorescent or LF detection systems targeting the S. mansoni mitochondrial minisatellite region. The specificity was assessed using gDNA from other Schistosoma species, helminths co-endemic with S. mansoni, human stool and urine, and Biomphalaria snail hosts. The analytical sensitivity was evaluated using serial dilutions of gDNA, synthetic copies of the target, and single eggs. The ability of both assays to detect the S. mansoni DNA in human urine and stool samples was also tested. The long-term stability of the RT-RPA reagents was evaluated by storing the reaction components in different temperature conditions for up to three weeks. Results: The RT- and the LF-RPA (SmMIT- and SmMIT-LF-RPA, respectively) presented similar results when used full- and half-volumes, thus the latter was followed in all experiments. The SmMIT-RPA was 100% specific to S. mansoni, able to detect a single egg, with a limit of detection (LOD) of down to 1fg of gDNA and one synthetic copy of the target. The assay was able to detect S. mansoni DNA from stool containing 1 egg/g and in spiked urine at a concentration of 10fg/µl. SmMIT-RPA reagents were stable for up to three weeks when kept at 19°C, and two weeks when stored at 27°C. The SmMIT-LF-RPA cross-reacted with Clinostomidae, presented the LOD of 10fg and one synthetic copy of the target, being able to detect a single egg and 1egg/g in a stool sample. The LOD in spiked urine samples was 10pg/µl. Conclusion: The half-volume SmMIT-RPA is a promising method to be used in the field. It is specific, sensitive, robust, and tolerant to inhibitors, with the long-term stability of the reaction components and the real-time visualisation of results.